2011
DOI: 10.4167/jbv.2011.41.2.65
|View full text |Cite
|
Sign up to set email alerts
|

Infectobesity: a New Area for Microbiological and Virological Research

Abstract: Obesity is connected with numerous diseases, such as type 2 diabetes, atherosclerosis, cancer, and nervous system dysfunctions. Obesity is affected by genetic, environmental, and cultural factors. However, numerous studies indicate that several pathogens might cause obesity. This review discusses recent data and the characteristics of pathogens that are implicated in obesity. In particular, human adenovirus 36 (Ad36) is the most clearly implicated virus in human obesity. It was recently shown that obese groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…On the other hand, as virus can lead to infectobesity, H. pylori may be a contributing factor to obesity. The virus induces obesity probably by means of interacting with the hypothalamic-pituitary-adrenal axis [30], while the possible mechanisms of H. pylori-induced obesity include interruption of leptin secretion, glucose uptake, and inflammation [31], H. pylori infection can induce chronic low-grade inflammation, and then prolonged, low-level immune stimulation induces hypertrophy of adipose tissue and increases shunting of energy to host defense mechanisms [32]. Our study found that the FPG, TG, LDL-C, and TC levels were higher in H. pylori-positive subjects than those in H. pylorinegative subjects.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, as virus can lead to infectobesity, H. pylori may be a contributing factor to obesity. The virus induces obesity probably by means of interacting with the hypothalamic-pituitary-adrenal axis [30], while the possible mechanisms of H. pylori-induced obesity include interruption of leptin secretion, glucose uptake, and inflammation [31], H. pylori infection can induce chronic low-grade inflammation, and then prolonged, low-level immune stimulation induces hypertrophy of adipose tissue and increases shunting of energy to host defense mechanisms [32]. Our study found that the FPG, TG, LDL-C, and TC levels were higher in H. pylori-positive subjects than those in H. pylorinegative subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Although the triggering role of Ad-36 in the Ad-36-obesity relationship is explained by these mechanisms, considering the replication potential and persistence of the virus in the host cell, other mechanisms may also impact the development and progression of obesity. Chronic inflammation process has been proposed to such a contributing mechanism [24,30].…”
Section: Directionmentioning
confidence: 99%
“…Immune cells and macrophages infiltrate the adipocytes and remodeling of adipose tissue develops because of angiogenesis. The infiltrated macrophages secrete IL-6, IL-8, TNF-a and MCP-1 and adipocytes lose homeostasis of the free acid pathway during the inflammatory state [30].…”
Section: Directionmentioning
confidence: 99%
“…Human adenovirus 36 infection has been shown to increase adiposity in both human and animal model systems . In addition, we have determined that Ad36 infection also increases inflammation in adipose tissues and maintains obesity states .…”
mentioning
confidence: 94%
“…In this study, we used Ad36 as a trigger for inflammation and obesity because Ad36 infection induces chronic inflammation that may contribute to increased adiposity in animals and humans (1)(2)(3)(4)(5). However, there are no currently available specific treatments or vaccines for Ad36-induced obesity.…”
mentioning
confidence: 99%